EDUKASI BENCANA KEKERINGAN DAN KESIAPSIAGAAN WARGA MASYARAKAT DALAM MENANGGULANGI BENCANA KEKERINGAN DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Ida Surya Surya; I Gusti Ngurah Suwetha (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2021)
Geologically, Indonesia is located at the confluence of three of the world's main plates, namely the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate, which often cause disasters, for example drought. Central Lombok Regency is one of the regencies in West Nusa Tenggara, with these two seasons, most often hit by drought disasters, considering that the rainfall in Central Lombok is very small. So that disaster education and preparedness are needed for residents. This article uses qualitative research methods. The results of the study show that climate field schools have an important role in disaster education. Climate field school is a form of education for farmers that is very useful especially in understanding the weather and climate combined with new agricultural techniques that will allow farmers to plant different crops at different times of the year. Meanwhile, for preparedness, it is carried out through several programs in the form of urging and asking farmers to be disciplined in carrying out cropping patterns according to the zoning in which they are located (rice-padi-palawija or padi-palawija-palawija), mapping of land related to cropping patterns, planting rice parity that requires little water, namely the Situpagendit variety, and urges farmers to insure their rice plants, which is Rp. 36.000/ Ha for one planting season at PT. JASINDI. Keywords: Indonesia's geological location, disaster, disaster education.